The Influence of Work Abilities, Work Motivation, Work Culture, Work Environment and Work Coordination on Ship Crew Performance - Onny Dwi Setiyono; Hary Sulaksono; Tamriatin Hidayah (Trescode Green Organization, 2024)
The International Safety Management Code or commonly known as the ISM Code or short for is an international standard for the Safety Management System for the safe operation of ships and efforts to prevent pollution at sea. The aim of implementing the ISM Code is to ensure safety at sea to avoid accidents that can cause loss of life and damage to ships that can cause environmental pollution at sea. SOLAS (Safety of Life at Sea) in 1994 adopted the ISM Code which is a product of the IMO (International Maritime Organization) The respondents for this research were 70 people consisting of ship crew members and office staff of PT. Atosim Lampung Pelayaran in 2024. Taking respondents consisting of ship crew members and office staff was aimed at finding an overview of HR competencies and communication patterns between them in carrying out work tasks. The performance of employees, especially crew members of the PT. ALP Banyuwangi Branch, is at a good level based on research results. That the variables Motivation and Coordination simultaneously have a significant effect on the performance of the crew members of the PT. ALP Banyuwangi Branch ship.